2014
DOI: 10.2147/ccid.s61659
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of a water-soluble nail lacquer based on hydroxypropyl-chitosan (HPCH), in the management of nail psoriasis

Abstract: BackgroundNail psoriasis occurs in up to 50% of patients affected by psoriasis, with a significant impact on quality of life that leads to a real clinical need for new therapeutic options.AimTo confirm whether the strengthening and hardening properties of the hydroxypropyl-chitosan (HPCH) nail lacquer could improve the structure of the nail plates on psoriatic nails.Materials and methodsA randomized, double-blind, placebo controlled, parallel-group trial was carried out to evaluate the efficacy and tolerabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…This water-based HPCH solution forms a protective film that remineralizes and restructures nails, protects keratin, and maintains hydration. In clinical studies, it has been shown to reduce the signs of fragility and roughness in the nails of patients with psoriatic nail dystrophy (7)(8)(9). The HPCH-based nail solution is not intended as a cure for onychomycosis, as it does not exhibit antifungal activity; instead, it is able to form a film on the nail surface that may prevent fungal invasion.…”
mentioning
confidence: 99%
“…This water-based HPCH solution forms a protective film that remineralizes and restructures nails, protects keratin, and maintains hydration. In clinical studies, it has been shown to reduce the signs of fragility and roughness in the nails of patients with psoriatic nail dystrophy (7)(8)(9). The HPCH-based nail solution is not intended as a cure for onychomycosis, as it does not exhibit antifungal activity; instead, it is able to form a film on the nail surface that may prevent fungal invasion.…”
mentioning
confidence: 99%
“…Colloidal drug delivery systems (including nail lacquers, adhesive patches, and gels) have attracted attention in recent years due to advantages in the enhancement of nail hydration because of their occlusive properties and long residence time. 7 A randomized, double-blind, placebo-controlled, parallelgroup trial confirmed the superior effectiveness and tolerability of a hydrosoluble nail lacquer containing hydroxypropyl-chitosan, Equisetum arvense, and methylsulfonylmethane; 11 the hydroxypropyl-chitosan nail lacquer achieved a significantly better clinical cure rate than placebo in both the intention-to-treat and per-protocol populations. 11 The use of novel hydrophilic formulations to treat nail psoriasis is promising, but the research work and commercialization in developing a highly effective topical delivery system is still lagging.…”
Section: Penetration Enhancement Strategies For Topical Therapymentioning
confidence: 91%
“…A topical agent such as nail lacquer represents a valid topical formulation to prevent fungal infections compared to creams and solutions, since it favors a better stay of the formulation at the site of action. Hydroxypropyl chitosan (HPCH), a semisynthetic derivative of chitosan, has proved to be a valid candidate for the delivery of active products to nails, acting as a protective film that preserves nail structure, protecting keratin, maintaining hydration with a decrease of dystrophy signs in psoriatic nails [174,175]. Two recent studies conducted by Cantoresi et al regarding the use of HPCH have shown the efficacy of the treatment of dystrophy in psoriatic nails by the association of the derivative chitosan with horsetail extract ( Equisetum arvense ) and methylsulphonyl-methane (DMSO 2 ).…”
Section: Applications In Cosmeticsmentioning
confidence: 99%
“…During the preliminary study, the efficacy of this formulation was identified and then confirmed by a secondary and randomized placebo-controlled double-blind trial. This research covered a period of 24 weeks where the synthesized product proved to have been statistically superior to placebo [174,176]. Ghannoum et al exemplify the effects of a HPCH-based nail solution compared to urea and isopropyl alcohol effects on the bovine hoof structure.…”
Section: Applications In Cosmeticsmentioning
confidence: 99%